1996
DOI: 10.1017/s0022112096002807
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence measurements around a mild separation bubble and downstream of reattachment

Abstract: This paper describes the behaviour of a turbulent boundary layer on a smooth, axisymmetric body exposed to an adverse pressure gradient of sufficient strength to cause a short region of mean reverse flow ('separation’). The pressure distribution is tailored such that the boundary layer reattaches and then develops in a nominally zero pressure gradient. Hot-wire and pulsed-wire measurements are presented over the separated region and downstream of reattachment. The response of the turbulence quantities to separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
42
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 17 publications
11
42
0
Order By: Relevance
“…5), which is in agreement with the enhancement of the Reynolds stresses downstream of a laminar separation, as reported by Castro and Epik (1998). Moreover, the order of magnitudes of the Reynolds stresses is consistent with results obtained just behind a turbulent separation (Alving and Fernholz 1996). The fact that the overall level of each Reynolds stress is higher than expected for a canonical turbulent boundary layer, and that these levels are still decreasing at the downstream edge of the measurement domain (x/d 0 = 28), indicates that the boundary layer remains affected by the trip at least up to there.…”
Section: Reynolds Stressessupporting
confidence: 91%
“…5), which is in agreement with the enhancement of the Reynolds stresses downstream of a laminar separation, as reported by Castro and Epik (1998). Moreover, the order of magnitudes of the Reynolds stresses is consistent with results obtained just behind a turbulent separation (Alving and Fernholz 1996). The fact that the overall level of each Reynolds stress is higher than expected for a canonical turbulent boundary layer, and that these levels are still decreasing at the downstream edge of the measurement domain (x/d 0 = 28), indicates that the boundary layer remains affected by the trip at least up to there.…”
Section: Reynolds Stressessupporting
confidence: 91%
“…Similarly to the present study, Alving and Fernholz (1996) concluded that the relaxation process is controlled by the outer energetic motions (wake-driven) in a way that it is not usually seen in canonical boundary layers, whose growth can be described by the wall-driven mechanism.…”
Section: Revisiting Some Literaturesupporting
confidence: 85%
“…Two further studies in which there are no trips involved are Alving and Fernholz (1996) and Castro and Epik (1998) who studied the boundary layer formed downstream of a recirculation bubble. This recirculation was generated by an adverse pressure and a blunt trailing edge respectively.…”
Section: Revisiting Some Literaturementioning
confidence: 99%
“…On the contrary, shed vortices with vorticity in z, i.e. the recirculation-like structures present for the Saw case and also reported in Alving and Fernholz (1996) and Castro and Epik (1998), would enhance the wake influence on the wall generating a wake-driven mechanism.…”
Section: Discussionmentioning
confidence: 70%
“…These trips with non-uniform blockage create a distorted wake which, after an adaptation region, may influence the formation of the inner structures up to a larger extent than in the former case, where the inner structures may not be as disturbed due to the low blockage at y = 0. This influence of the wake in the near-wall region has also been reported as a characteristic of re-attached flows downstream of a separation (Alving and Fernholz 1996;Castro and Epik 1998). Different heights and degrees of immersion in the boundary layer are tested in order to assess the influence of these parameters on the recovery length for canonical properties of the generated boundary layer.…”
Section: Introductionmentioning
confidence: 86%